Evaluation of Dendrobium Hybrids for Growth and Yield under Lower Hills of Nagaland - Thirugnanavel, A.; Deka, Bidyut C.; Rengnamei, Lily (Indian Journal of Hill Farming, 2019)
An experiment was conducted to evaluate the tropical Dendrobium hybrids under lower hills of Nagaland for their performance at ICAR Research Complex for NEH Region, Nagaland Centre, Nagaland. Seven Dendrobium hybrids namely Snow White, Genting Blue, Genting Red, Woon Leng, Massaco, Pink Ruby and Juwita were evaluated for vegetative and flower characters. The results of the experiment revealed that Snow White recorded maximum pseudobulb height (53.7 cm), internode length (6.3 cm), leaf length (17.8 cm), leaf breadth (4.1), and number of florets per spike (8.4), whereas Juwita recorded maximum number of pseudobulbs per plant and Pink Ruby recorded the maximum spike length (39.7 cm). It is concluded that Snow white and Juwita were performed better under Nagaland Condition.